Debunking the Stereotype of the Lazy Welfare Recipient : Evidence from Cash Transfer Programs - Banerjee, Abhijit V. (Published by Oxford University Press on behalf of the World Bank, 2019)
Targeted transfer programs for poor citizens have become increasingly common in the developing world. Yet, a common concern among policy-makers and citizens is that such programs tend to discourage work. We re-analyze the data from seven randomized controlled trials of government-run cash transfer programs in six developing countries throughout the world, and find no systematic evidence that cash transfer programs discourage work.